Understanding Nationalism in Historical Places: A Study of the Museum Visit Experience of Civic Education Students of Universitas Ahmad Dahlan - Annisa Rahmania; Dikdik Baehaqi Arif; Mahmuda Ma'arif (Universitas Muhammadiyah Surakarta, 2026)
The research was inspired by the importance of nationalist values in history learning, particularly at a time when visiting museums is frequently regarded merely as a form of entertainment. The Katadata Insight Center has reported that 67.2% of museum visits are for recreational purposes, indicating that museums have not fully optimized their educational function. This research aims to reveal students’ interpretations of and reflections on the nationalist values they develop after visiting museums. This study adopts a qualitative approach with a phenomenological design. Data were collected using in-depth interviews and documentation, and and subsequently analyzed via thematic analysis. The subjects included the lecturer of the Indonesian National History course and six students from the Pancasila and Civic Education (PPKn) study program selected through purposive sampling. The findings reveal that museum visits engender a transformation of perspective toward history, a transfer of values, historical visual validation, a spiritual connection, and professional reflection for pre-service teachers. The experience encourages students to reflect on nationalism, as indicated by a redefinition of nationalism, increased historical awareness, an internalization of sacrifice, and changes in social behavior. The findings also show that an understanding of nationalism is shaped by students' interpretations of and reflections on their experiences during museum visits. These insights can serve as a reference for developing experience-based materials for history courses in higher education.